QUALITY OF LIFE IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE: importance of clinical, demographic and psychosocial factors - MAGALHÃES,Joana (2014)
Context Inflammatory bowel disease causes physical and psychosocial consequences that can affect the health related quality of life. Objectives To analyze the relationship between clinical and sociodemographic factors and quality of life in inflammatory bowel disease patients. Methods Ninety two patients with Crohn’s disease and 58 with ulcerative colitis, filled in the inflammatory bowel disease questionnaire (IBDQ-32) and a questionnaire to collect sociodemographic and clinical data. The association between categorical variables and IBDQ-32 scores was determined using Student t test. Factors statistically significant in the univariate analysis were included in a multivariate regression model. Results IBDQ-32 scores were significantly lower in female patients (P<0.001), patients with an individual perception of a lower co-workers support (P<0.001) and career fulfillment (P<0.001), patients requiring psychological support (P = 0.010) and pharmacological treatment for anxiety or depression (P = 0.002). A multivariate regression analysis identified as predictors of impaired HRQOL the female gender (P<0.001) and the perception of a lower co-workers support (P = 0.025) and career fulfillment (P = 0.001). Conclusions The decrease in HRQQL was significantly related with female gender and personal perception of disease impact in success and social relations. These factors deserve a special attention, so timely measures can be implemented to improve the quality of life of patients.